Regenerasi Pepaya melalui Kultur In Vitro - Diani Damayanti; Sudarsono Sudarsono; Ika Mariska; M. Herman (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2007)
A study was conducted in the Indonesian Center forAgricultural Biotechnology and Genetic Resources Researchand Development to optimize papaya regeneration systemsthrough in vitro culture. Four steps were done, i.e., callusinduction, callus regeneration, root formation, and acclimatization.Explant materials used were immature embryos ofpapaya cv. Burung. Immature papaya embryos were culturedon different media. The best medium for embryogeniccallus development was ½ MS + 10 mg/l 2.4-D + 60% sucrose+ 143 mg/l adenine sulphate + 50 mg/l myo inositol +400 mg/l glutamine, while that for callus embryo regenerationwas MS + 0.5 mg/l GA3 + 0.1 mg/l kinetin + Morel andWetmore Vitamin. Using this medium, the average of shootformation was three shoots per explant of embriogeniccallus, and the percentage of regenerated callus was 80%.The color of shoot derived from this treatment was green.Eighty percent of plants formed a complete root developmentusing ½ MS + 0.5 mg/l paclobutrazol media. Media hullof rice and compost was the best medium for papaya plantacclimatization. The percentage of survival on that acclimatizationstep was 65%.